The crystallization of a superfluid: the supersolid - Antolini, Nicolò; Biagioni, Giulio (Il Colle di Galileo, 2022)
Superfluids can become crystals, obtaining rigidity and plasticity in analogy with classical solids, but keeping their typical properties of quantum coherence. The resulting phase is a supersolid, recently observed experimentally in a dipolar quantum gas. We have studied the phase transition from the superfluid to the supersolid, highlighting the analogies and differences with the corresponding classical transition from liquid to solid.